EVALUATION OF THE INFLUENCE OF THE DRUG «CARNITIN» ON THE PERIPHERAL BLOOD - Elena Olegovna Sergeeva; Alexander Yurievich Terekhov; Elena Panteleevna Parfentyeva; Svetlana Grigoryevna Tiraspolskaya; Lubov Anatolievna Sadjaya (Современная наука и инновации)
In the article results of experimental researches of influence of carnatine in the peripheral blood. Cherniatyn (acetyl-L-carnitine) - metabolic drugs, protecting brain tissue from ischemia; slows the aging process. As a result of the study showed that the peripheral blood picture remains unchanged after long-term use, and after its cancellation (after 14 days) after oral administration and at a dose of300 mg/kg and at a dose of3000 mg/kg.